Multitechnique Geochronology of Intrusive and Explosive Activity on Piton des Neiges Volcano, Réunion Island. (5th May 2022) - Famin, Vincent; Paquez, Camille; Danišík, Martin; Gardiner, Nicholas J.; Michon, Laurent; Kirkland, Christopher L.; Berthod, Carole; Friedrichs, Bjarne; Schmitt, Axel K.; Monié, Patrick
Abstract: The construction of ocean island basaltic volcanoes consists of a succession of eruptions, intrusions, and metamorphism. These events are often temporally ill‐constrained because the most widely used radiometric dating methods applicable to mafic volcanic rocks (K‐Ar or 40 Ar/ 39 Ar on whole rock or groundmass) are prone to inaccuracy when applied to slowly cooled, altered, or vesicular and aphyric products. Here, we adopt a multitechnique geochronology approach (including zircon U‐Pb, phlogopite 40 Ar/ 39 Ar, zircon and apatite (U‐Th)/He, and zircon double‐dating) to demonstrate its efficacy when applied to basaltic volcanoes. Taking the main volcano of Réunion Island (Piton des Neiges) as a case study, we establish the time of the major plutonic, metamorphic, and explosive events that had resisted previous dating attempts. We document four stages of pluton emplacement and metamorphism at 2, 200–2, 000 ka, 1, 414 ± 8 ka, 665 ± 78 ka, and 150–110 ka, all coinciding with volcanism revival after quiescent intervals. We also date a major Plinian eruption at 188.2 ± 10.4 ka, coeval with the formation age of a large caldera, and, finally, we constrain the last eruption of Piton des Neiges to 27 ka, revising a previous estimate of 12 ka. By resolving several conundrums of Réunion's geological history, our multitechnique geochronology approach reveals that endogenous growth of a volcanic island proceeds as pulses at the beginning of renewed volcanism. We also demonstrate that crosschecking eruptions ages by diversified dating techniques is important to better assess the timing and recurrence of basaltic volcanic activity, with implications for hazard prediction. Plain Language Summary: Dating techniques based on natural radioactivity span multiple isotopes and minerals. However, geochronology of volcanic islands remains challenging due to the extremely low radioactivity of erupted products—mostly basalts (including their mineral cargo). Consequently, many events in the geological history of these islands, like explosive eruptions or magma intrusions, remain challenging to date. To resolve this issue, we test the efficacy of six dating methods, unusually applied to a basaltic volcanic island and never in combination. Taking Piton des Neiges volcano (Réunion Island) as a natural laboratory, we demonstrate that combining these techniques is not only feasible, but also productive in terms of the recovered geological information. We obtain ages for many rocks of Réunion that resisted other techniques, or whose age has previously remained controversial. In particular, we date a major explosion at 188, 000 years, and constrain the last eruptive activity of Piton des Neiges to 27, 000 years, revising a previous estimate of 12, 000 years. The new ages also show that significant volumes of magma must have remained stored inside the edifice at the beginning of active periods. Our combined approach thus offers a promising solution to reconstruct the history of volcanic islands and better predict their hazard. Key Points: First application of zircon‐phlogopite‐apatite geochronology to a hotspot island Endogenous growth proceeds as pulses at the beginning of renewed volcanism Last volcanism of Piton des Neiges is 27 ka, not 12 ka as earlier proposed